2019
DOI: 10.1128/mra.01187-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Vibrio campbellii DS40M4

Abstract: We present the complete genome sequence of Vibrio campbellii DS40M4, assembled from Illumina and Oxford Nanopore data. This effort improves upon a previous draft assembly to resolve this organism’s two-chromosome and one-plasmid genetic structure and to provide valuable context for evaluating the gene arrangement and evolution of this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…However, while it is understood and accepted that strains of the same bacterial species can vary widely in nature, it is not often investigated how the canonical models diverge among these strains. Although BB120 and DS40M4 are very closely related (Colston et al ., 2019), we have shown that these two strains differ widely from one another in natural transformation, quorum‐sensing pathways, and various other phenotypes. It is important to consider strain to strain variations and how bacteria in the environment may differ from the models established from laboratory strains.…”
Section: Discussionmentioning
confidence: 93%
“…However, while it is understood and accepted that strains of the same bacterial species can vary widely in nature, it is not often investigated how the canonical models diverge among these strains. Although BB120 and DS40M4 are very closely related (Colston et al ., 2019), we have shown that these two strains differ widely from one another in natural transformation, quorum‐sensing pathways, and various other phenotypes. It is important to consider strain to strain variations and how bacteria in the environment may differ from the models established from laboratory strains.…”
Section: Discussionmentioning
confidence: 93%
“…cholerae exhibit differing natural transformation frequencies (15, 16), we hypothesized that the absence of competence in BB120 may not be indicative of competence in other V. campbellii isolates. We therefore assayed natural transformation in three V. campbellii environmental isolates with sequenced genomes: DS40M4, NBRC 15631, and HY01 (21, 2326). DS40M4 was isolated from the Atlantic Ocean near the west coast of Africa (26), HY01 was isolated from a bioluminescent shrimp in Thailand (24), and NBRC 15631 (also called CAIM 519 and ATCC 25920) was isolated from seawater in Hawaii (21).…”
Section: Resultsmentioning
confidence: 99%
“…However, while it is understood and accepted that strains of the same bacterial species can vary widely in nature, it isn't often investigated how the canonical models diverge amongst these strains. Although BB120 and DS40M4 are very closely related (Colston et al, 2019), we have shown that these two strains differ widely from one another in natural transformation, quorum-sensing pathways, and various other phenotypes. It is important to consider strain to strain variations and how bacteria in the environment may differ from the models established from laboratory strains.…”
Section: Discussionmentioning
confidence: 84%
“…We hypothesized that these environmental V. campbellii strains may exhibit differences in other behaviors such as growth and quorum sensing-controlled phenotypes. Here, we show that the recently sequenced environmental isolate V. campbellii DS40M4 (1618) exhibits several advantages as a model organism compared to BB120. Using natural transformation to rapidly construct mutants, we tested differences in quorum sensing-controlled phenotypes between DS40M4 and BB120, including biofilm formation, T6SS-mediated cell killing, protease activity, and bioluminescence.…”
Section: Introductionmentioning
confidence: 91%